Study on Dynamic Response of Pile Foundation in Elastoplastic Soil Under Horizontal Loads - Gu, Xiaoqing; Shu, Jiaqing; Wang, Yuxuan; Wang, Pengpeng; Zhu, Mingxing (Buildings (Basel), 2024)
The elastoplastic model can more accurately simulate the elastoplastic behavior of soil in the process of loading, so as to determine the soil resistance more accurately, which holds great significance in calculating the bearing capacity of pile foundations. However, the current study has not found that the elasticity of soil is taken into account to analyze the dynamic behavior of pile foundations. To study the dynamic response of pile foundation under horizontal cyclic load, theoretical calculation methods and model tests are applied. Based on the flexural differential equation of pile and considering the inertia force of the pile under harmonic load, the analytical solutions for the displacement and bending moment of pile foundation under horizontal cyclic load are obtained. The accuracy of the calculation method is confirmed through comparison with experimental results. An analysis is conducted to examine the impacts of harmonic load amplitude and frequency, foundation reaction coefficient, and pile bending stiffness on the plastic height. The changing rules of the pile bending moment and pile displacement with harmonic load amplitude, foundation reaction coefficient, and pile bending stiffness are studied. By comparing the theoretical and experimental results with numerical methods, it is found that the general trend of the experimental and theoretical results is consistent. It is found that as the harmonic load frequency increases, the foundation reaction coefficient decreases, and the harmonic load amplitude increases, there is a corresponding augmentation in the plastic height of the soil, pile displacement, and bending moment.